The objectification of adulthood of persons with deeper and deep intellectual disability - Prysak, Dorota (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Dorota Prysak, The objectification of adulthood of persons with deeper and deep intellectual disability. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 237–254. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.11 The adulthood of persons with deeper and deep disability continues to be a challenge not only for specialists and parents or caretakers of the indicated group of persons, but also for us as a society. The objective of the article is the presentation of effects of activities experienced by adults with deeper and deep intellectual disability while inhabitants of a social nursing home. One of the main effects of the mentioned activity is objectification. In the discussed case, the objectification is the effect of lack of trust or limited trust in their potential, which can become a factor of manipulation. The research material used in the present study constitutes personal experiences gained while working with persons with deeper and deep intellectual disability, their caretakers, parents and other specialists working with them, acquired through participation in diverse activities/ projects aimed at them. Free, narrative discussions as well as focused discussions were conducted with representatives of the indicated groups (save for persons with deep, and in certain cases, significant intellectual disability). The analysis of the research material was conducted according to the action research methodology.